Analisis Implementasi Kebijakan Identitas Kependudukan Digital (IKD) dalam Meningkatkan Kualitas Pelayanan Publik di Indonesia - Anisa Ramadani; Nebilla Sauda Azzahra; Abdal (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Digital transformation in public services has encouraged the Indonesian government to introduce various innovations, including the implementation of Digital Population Identity (Identitas Kependudukan Digital/IKD). This policy aims to improve the efficiency of population administration while enhancing the quality of digital-based public services. This study examines the implementation of the IKD policy in improving public service quality in Indonesia and identifies the supporting and inhibiting factors affecting its implementation. The research employs a qualitative descriptive approach through a literature review of academic journals, books, government documents, and other relevant scholarly sources. The findings indicate that IKD contributes to faster identity verification, easier access to public services, improved administrative efficiency, and better integration of population data. Nevertheless, its implementation continues to face several challenges, including limited digital infrastructure, low levels of digital literacy, unequal access to technology across regions, and concerns regarding personal data security. The effectiveness of IKD implementation is largely influenced by infrastructure readiness, human resource capacity, institutional commitment, and public acceptance of digital technology. Therefore, continuous efforts are required to strengthen digital infrastructure, improve digital literacy, and enhance personal data protection in order to maximize the benefits of IKD in creating more effective, efficient, transparent, and integrated public services.